Diagnostic Concordance of Histologic Lung Cancer Type Between Bronchial Biopsy and Cytology Specimens Taken During the Same Bronchoscopic Procedure. - Sackett, Melanie K.; Salomão, Diva R.; Donovan, Janis L.; Yi, Eunhee S.; Aubry, Marie Christine (Archives of Pathology & Laboratory Medicine, 2010)
Context.--The diagnosis of lung cancer is often confirmed by cytology and biopsy specimens obtained during a bronchoscopic procedure. At our institution, these specimens are read by different pathologists, and the rate of concordance was not known. Objectives.--To evaluate the concordance rate in the diagnosis of lung cancer types between cytology and biopsy specimens and to correlate discordancewith patient outcome. Design.--Specimens obtained during the same procedure, between January 1, 2000, and December 31, 2005, were identified. Cases with cytology and biopsy specimens positive for cancer were evaluated for concordance of histologic type, small cell versus non-small cell lung carcinoma. Cases with different types were considered discordant, and slides were reviewed. Results.--Of 231 cases, 225 (97.4%) had concordant diagnoses. Discordance was the result of misinterpretation of undifferentiated carcinoma, overinterpretation of squamous dysplasia, interpretation of suboptimal specimens with necrosis and crush artifact, and sampling error. Conclusions.--Even though the cytology and biopsy specimens were reviewed by different pathologists, the concordance rate for histologic type at our institution was high, emphasizing that this is a safe practice. The few discordant cases did not affect the patient's outcome.